IMPLEMENTASI PEMBELAJARAN KITAB TA’LIM AL-MUTAALLIM DALAM PEMBENTUKAN AKHLAK SISWA DI MTs AT-TAUFIQ BOGEM GROGOL DIWEK JOMBANG - latifa, Dinda Nurul; Said, Ali (EL-Islam, 2022)
Abstract: This research is based on the nature of the task as a human being, namely in the teachings of Islamic education to achieve perfect morals. In education, educators are also obliged to give advice and special attention in shaping their personality. However, moral education is often neglected in school learning, so it will become a critical problem in schools and educators. This research was conducted at MTs At-Taufiq Bogem Grogol Diwek Jombang. The research objectives are to describe: 1). Learning the book of Ta'lim Al-Muta'allim in moral formation at MTs At-Taufiq Bogem Grogol Diwek Jombang 2). Implementation of learning the book Ta'lim Al-Muta'allim in moral formation at MTs At-Taufiq Bogem Grogol Diwek Jombang 3). Supporting and Inhibiting Factors in learning the book of Ta'lim Al-Muta'allim in moral formation at MTs At-Taufiq Bogem Grogol Diwek Jombang. This research includes a qualitative approach, using a descriptive method. Researchers as the main research instrument, by acting as a passive observer. The data used are primary and secondary data. Collecting data used through observation, interviews and documentation. Checking the validity of the data used is triangulation of sources and methods. The conclusions of this study are (1) Learning at MTs At-Taufiq using the Pondok Salaf and Sorogan methods. (2) Implementation in MTs At-Taufiq can already be seen from the students, seen from the way they welcome the teacher and often help the teacher. (3) Supporting Factors, namely: a good explanation from the teacher and assisted by the student madrasa, from the lessons taught, assisted by intra and ekstra school activities, some students have books, supporting infrastructure, there are religious activities in madrasa; Some teachers who are not active in school activities, difficult to condition students, inhibiting factors, namely: weak student learning, family factors, environmental factors, students who do not have books to study at home.